DISTAL TIBIAL RECONSTRUCTION WITH INTRAMEDULLARY NAIL COMBINED WITH T-PLATE FOLLOWING EN-BLOC-EXCISION OF GIANT CELL TUMOR OF DISTAL TIBIA: CASE-REPORT - Mujaddid Idulhaq; Fajar Baskoro Gardjito; Ibnu Yudistiro (Journal Orthopaedi and Traumatology Surabaya, 2021)
Background: Giant cell tumor is locally aggressive benign tumor that occur more common in distal femur, proximal tibia, and distal radius, and has tendency for recurrence and has capability for metastatize. Giant cell tumor in foot ankle are rare, and comprise less than four percent of giant cell tumor of the bone.Case Report: A 33 years old man presented with complains of pain and swelling in right ankle since 6 months ago with no history of trauma. Physical examination revealed increasing swelling over the distal-posteromedial aspect of lower leg and limitation ankle movements due to pain. Routine blood investigations showed slight increase of alkaline phosphatase. X-ray and Magnetic Resonance Imaging showed the lesion with morphology suggestive of giant cell tumor. Histopathology examination showed multinucleated giant cells and spindle shaped of mononuclear cells suggestive of giant cell tumor. The patient was treated with en-bloc-excision followed with distal tibial reconstruction using reverse intramedullary tibial nail combined with T-plate (tibio-talar arthodesis).Discussion: The main treatment of giant cell tumor of the bone is surgical removal to achieve tumor-free by eradication of the tumor, with various surgical techniques for reconstructing the cavity left. In this case we performed distal tibial reconstruction using reverse intramedullary tibial nail combined with T-plate.Conclusion: The patient at 12-month follow up is doing well, walking comfortably without any pain, has no limitation in range of motion with no signs of recurrence and good MSTS score (90).